2004
DOI: 10.1007/s00432-003-0500-4
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of MMP-2 and MMP-9 in esophageal squamous cell carcinoma.

Abstract: Increased levels of MMP-2 and MMP-9 proteins in ESCCs as compared to normal esophageal tissues suggest their association with esophageal tumorigenesis. Increased levels of these MMPs are observed in majority of dysplasias analyzed herein, indicating that these alterations may be early events in esophageal tumorigenesis. In-depth studies are warranted to determine their role in development and progression of esophageal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
80
0
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(94 citation statements)
references
References 30 publications
6
80
0
5
Order By: Relevance
“…Here other proteases and its inhibitors along with cytokines and growth factors could have played an important role. In the present study expression of MMP-2 and TIMP-2 was not evident in keratinocytes and fibroblasts in the normal buccal mucosa which was in accordance to the other studies by Sutinen et al, Hong Q et al and Samantaray et al 18,27,28 Only the endothelial cells were found to be positive to MMP-2 and TIMP-2, which is needed to maintain tissue homeostasis.…”
supporting
confidence: 93%
“…Here other proteases and its inhibitors along with cytokines and growth factors could have played an important role. In the present study expression of MMP-2 and TIMP-2 was not evident in keratinocytes and fibroblasts in the normal buccal mucosa which was in accordance to the other studies by Sutinen et al, Hong Q et al and Samantaray et al 18,27,28 Only the endothelial cells were found to be positive to MMP-2 and TIMP-2, which is needed to maintain tissue homeostasis.…”
supporting
confidence: 93%
“…The development of malignant neoplasms is a long-term and multi-step process, which results in rapid growth and invasion of tumor cells into lymphatic and blood vessels [18]. The first step of tumor development and metastasis is the proteolysis of microvessel basement membranes and invasion of endothelium.…”
Section: Matrix Metalloproteinases (Mmps)mentioning
confidence: 99%
“…It has been proved that these enzymes are involved in the development of many malignant neoplasms: gastric, colorectal, pancreatic and breast cancer [40][41][42][43]. High MMP-9 protein expression in tumor tissues of EC patients has been shown in several studies [4,18,[44][45][46][47]. Percentages of MMP-9 positive immunostaining (diagnostic sensitivity) in esophageal cancer tissue reached 78% in the study by Murray et al [44] and increased with tumor stage.…”
Section: Mmp-9mentioning
confidence: 99%
“…Development of malignant tumors is a long-term and multi-step process resulting in rapid growth and invasion into lymphatic and blood vessels [7]. The migration of tumor cells depends on the degradation of the extracellular matrix, which can be regulated by complex control of the expression and activity of matrix metalloproteinases (MMPs), a family of zinc-dependent endopeptidases, and their natural inhibitorstissue inhibitors of matrix metalloproteinases (TIMPs) [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The migration of tumor cells depends on the degradation of the extracellular matrix, which can be regulated by complex control of the expression and activity of matrix metalloproteinases (MMPs), a family of zinc-dependent endopeptidases, and their natural inhibitorstissue inhibitors of matrix metalloproteinases (TIMPs) [7][8][9]. Remodeling of normal and tumoral tissue may be a result of aberrations in dynamic balance between MMPs and TIMPs.…”
Section: Introductionmentioning
confidence: 99%